Transformasi pembelajaran di sekolah dasar melalui Flipbook Maker: dampak terhadap keterlibatan siswa dan perubahan paradigma pendidikan - Prananda, Gingga; Judijanto, Loso; Atikah, Nur; Khoirunnisa, Qori; Fauzi, Muhammad Sukron (Universitas Muhammadiyah Magelang, 2025)
This study aims to examine the impact of using Flipbook Maker on student engagement and the shift in educational paradigms in elementary schools. The method used is a descriptive qualitative approach with a case study, involving interviews with teachers, classroom observations, and analysis of student learning product documents. The research results show that the use of Flipbook Maker significantly enhances student engagement in learning. Students become more active in participating, creative, and collaborative in creating learning materials. Additionally, the application of this technology also brings a shift in the educational paradigm, from a lecture-based teaching approach to a more interactive, project-based, and collaborative learning approach. This study also found that the use of Flipbook Maker contributes to the development of 21st-century skills such as critical thinking, communication, and creativity, as well as positively affecting learning outcomes. These findings are expected to provide new insights into the use of technology in education, particularly at the elementary school level, and encourage the broader adoption of technology in the learning process in elementary schools.